(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2022)
The article delves on the question about the movement and other ways of appropriating techno-social frameworks of the present. It develops a theoretical and reflexive systematization and update on approaches of differential experiences in virtual environments. The main themes for this purpose are spatialities, corporeality, agencies and appropriations of spaces and tools. This approach is based on theories such as technofeminism and social studies of technologies, especially the social constructionism perspectives. We use the theoretical tools of feminist and intersectional studies to explore on the notion of differential experiences. The conclusions offer situated proposals for conceptual frameworks, as possible ways of approaching on issues about digital technologies, diversity, access and equity.